Observation of Crack Propagation in Glass Using X‐ray Phase Contrast Imaging. (10th October 2014) - Parab, Niranjan D.; Black, John T.; Claus, Benjamin; Hudspeth, Matthew; Sun, Jianzhuo; Fezzaa, Kamel; Chen, Weinong W.
<x xml:space="preserve">Abstract</x> High‐speed X‐ray phase contrast imaging synchronized with a Kolsky bar apparatus was utilized to investigate the cracking behavior of a borosilicate glass, a soda lime glass, and a glass ceramic in front of a cylindrical projectile with an impact velocity of 5 ms−1. For each material, three different surface conditions were prepared for the impacted edge of the specimen. Angular cracking was observed in front of the projectile for borosilicate glass. For soda lime glass, straight cracking was observed. For glass ceramic, curved cracking was observed in front of the projectile. Cracking behavior was observed to be independent of the surface condition on the impacted edge.